Changing landscape of living kidney donation and the role of telemedicine. Issue 1 (21st January 2023) - Al Ammary, Fawaz; Muzaale, Abimereki D.; Tantisattamoa, Ekamol; Hanna, Ramy M.; Reddy, Uttam G.; Bunnapradist, Suphamai; Kalantar-Zadeh, Kamyar
Abstract : Purpose of review: There has been a decline in living kidney donation over the last two decades. Donors from low-income families or racial/ethnic minorities face greater disproportionate geographic, financial, and logistical barriers to completing lengthy and complex evaluations. This has contributed to the decreased proportion of these subgroups. The authors view telemedicine as a potential solution to this problem. Recent findings: Since the initial decline of donors in 2005, biologically related donors have experienced a lack of growth across race/ethnicity. Conversely, unrelated donors have emerged as the majority of donors in recent years across race/ethnicity, except for unrelated black donors. Disparities in access to living kidney donation persist. Telemedicine using live-video visits can overcome barriers to access transplant centers and facilitate care coordination. In a U.S. survey, nephrologists, surgeons, coordinators, social workers, and psychologists/psychologists across transplant centers are favorably disposed to use telemedicine for donor evaluation/follow-up beyond the coronavirus disease 2019 pandemic. However, with the waning of relaxed telemedicine regulations under the Public Health Emergency, providers perceive payor policy and out-of-state licensing as major factors hindering telemedicine growth prospects. Summary: Permanent federal and state policies that support telemedicine services for living kidney donation can enhance access to transplant centers and help overcome barriers to donor evaluation.